DOPUSZCZALNOŚĆ ROSZCZEŃ UZUPEŁNIAJĄCYCH SKIEROWANYCH PRZECIWKO POSIADACZOM SŁUŻEBNOŚCI - Jędrejek, Grzegorz (Zeszyty Prawnicze, 2017)
Admissibility of Complementary Claims of the Possessor of Servitude Summary According to art. 352 § 2 of the Civil Code the provisions of possessing an object apply correspondingly to possessing a servitude, including the provisions of so called complementary claims. In the author’s opinion, the owner is entitled to pursue complementary claims against the holder of the servitude only if deprived o f the control o f an object. The court should examine whether the owner was deprived of the object separately in every case. in the author’s view, the owner cannot pursue these claims in other instances of the disturbance of the right of the ownership. The jurisdiction and doctrine are consistent with regard to the criteria of establishing the owner’s remuneration for the object’s usage in case of the deprivation of the control thereof. Its amount should equal to that due from the object’s possessor having a legal title thereto.